Effect of nisin and lysozyme on bacteriological and sensorial quality of pasteurized milk - Saad, Marwa A; Ombarak, Rabee Alhossiny; Rabou, Hagar S Abd (Journal of Advanced Veterinary and Animal Research, 2019)
Objectives: The objective of this study was to evaluate the impact of the antimicrobials nisin and lysozyme to control the growth of spoilage bacteria of pasteurized milk during cold storage. Materials and Methods: Nisin, lysozyme, and a mixture of them were inoculated into freshly pasteurized milk at 500 IU/ml concentrations each. The acidity, sensory evaluation, and bacteriological quality of the treated pasteurized milk samples were examined at zero time and every 3 days till the samples showed the signs of spoilage, that were checked every day. Results: Obtained results showed that there was a slight increase of the titratable acidity of the control and treated samples during refrigerated storage, but the acidity increase was significantly lower in samples containing lysosomes and/or nisin than the control samples. Nisin and lysozyme at 500 IU/ml concentration possessed inhibitory effect on the total bacterial, aerobic spore-formers, and psychrotrophic bacterial counts and extended the shelf-life of the treated samples. The efficacy of nisin 500 IU/ml combined with lysozyme 500 U/ml was assessed and synergistic activity has been detected, that was expressed in the form of higher inhibitory effect and extending the shelf-life of the samples up to 15 days at cold storage. Moreover, the sensory evaluation showed that nisin and lysozyme does not affect the acceptability of the examined samples. Conclusion: The obtained data indicate that nisin and lysozyme have the potential to enhance the post-process bacteriological safety of pasteurized milk during the storage period and could aid in the elimination of post-process contamination and prolong its shelf-life. J. Adv. Vet. Anim. Res., 6(3): 403-408, September 2019